Policing in New Immigrant Communities - Matthew Lysakowski, Albert Persall, and Jill Pope (My University, 2016)
The common challenges that law enforcement agencies face when working with immigrant communities include language barriers, fear of police, and cultural differences, among others. To address these challenges and discuss promising practices for cultivating, maintaining, and restoring partnerships to keep communities safe, the Office of Community Oriented Policing Services, in partnership with the Vera Institute of Justice, sponsored a focus group comprising leading law enforcement leaders, experts, and community leaders from five jurisdictions in the United States. This report is based on that discussion.